2021
DOI: 10.1080/26895269.2021.1890659
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the first three months of the COVID-19 pandemic on the Australian trans community

Abstract: Background: Trans and gender diverse individuals (people who identify with a gender different to what was presumed for them at birth) are one of the most medically and socially marginalized groups in our community. The COVID-19 pandemic may compound preexisting depression and thoughts of self-harm or suicide. Aim: We aimed to explore the impact of the COVID-19 pandemic on the Australian trans community. Methods: An online cross-sectional survey was conducted between 1st May 2020 and 30th June 2020, amidst stri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…While some research regarding the COVID-19 pandemic and quality of life is starting to be published, results regarding the specific impact on trans communities are still rare. One study regarding the impact of the first three months of the COVID-19 pandemic on trans Australians (N = 1019) [ 3 ] found that 49% of respondents reported thoughts of self-harm or suicide and 61.5% experienced clinically significant symptoms of depression. Further, half their sample reported experiencing financial strain and almost a quarter (22.4%) were unemployed [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While some research regarding the COVID-19 pandemic and quality of life is starting to be published, results regarding the specific impact on trans communities are still rare. One study regarding the impact of the first three months of the COVID-19 pandemic on trans Australians (N = 1019) [ 3 ] found that 49% of respondents reported thoughts of self-harm or suicide and 61.5% experienced clinically significant symptoms of depression. Further, half their sample reported experiencing financial strain and almost a quarter (22.4%) were unemployed [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study regarding the impact of the first three months of the COVID-19 pandemic on trans Australians (N = 1019) [ 3 ] found that 49% of respondents reported thoughts of self-harm or suicide and 61.5% experienced clinically significant symptoms of depression. Further, half their sample reported experiencing financial strain and almost a quarter (22.4%) were unemployed [ 3 ]. More research is needed to better understand, and thus better serve, trans individuals during the current and future health crises.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 Their fear of being mistreated on the grounds of gender distinction causes stress, anxiety, and self-destructive behaviors. 9 The transgender community is at a fourfold higher risk of suicide. 10 This article highlights the possible contributing factors towards the increase in suicide rate in trans people in the light of the COVID-19 pandemic, as they are more vulnerable and sensitized to stress, resulting in a higher risk of poor psychosocial outcomes.…”
Section: Mental Health and Suicide Risk In Transgender Peoplementioning
confidence: 99%
“…There are limited data on the delivery of gender-affirming health care during the COVID-19 pandemic, including maintaining or starting gender-affirming hormone therapy and mental health counseling. However, the extant research suggests that telehealth helped maintain access to care in the United States and Australia, despite clinic-closures resulting from COVID-19 ( Zwickl et al, 2021 ; Lock et al, 2021 ). For example, clinical data from 10 family planning clinics in the U.S. suggested that telehealth maintained individuals’ access to gender-affirming care, while increasing the proportion of new patients seeking gender-affirming care ( Lock et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%